Acesso dos usuários à atenção primária à saúde no contexto da pandemia da COVID-19: um estudo de caso - Costa, Rafaela Pires Leal Cardoso (2023)
The Covid-19 pandemic came as a great challenge for health workers. Dealing with a hitherto unknown disease, which spread rapidly and caused an uncontrolled increase in the number of deaths, brought several discussions to world health in order to establish the best strategies to control the spread of the disease, reduce deaths and promote assistance in the different scenarios. The main objective of this study was to analyze user access to PHC health actions and services in the municipality of São Gonçalo dos Campos-BA, during the COVID-19 pandemic. It is a qualitative research, of the case study type. A semi-structured interview was used as a data collection technique. 17 people participated in the study, 14 health workers and 3 managers. For data analysis, the content analysis technique was used, with the support of the IRAMUTEQ software, through the similitude tree and word clouds. The study points out that different strategies were created to ensure user access to PHC actions and services in São Gonçalo dos Campos-BA, such as: adapting structures to ensure distancing, establishing prenatal consultations with scheduled times, organization of a dental shift at one of the service units, use of a telephone channel to follow up suspected cases and clarify doubts about the disease. In addition, the performance of professionals in sanitary barriers was highlighted as a preventive measure through guidance and identification of suspected cases. The research also signaled the importance of periodic training and discussion spaces, since it is a new disease. The study brings to health workers and managers when acting in the COVID-19 pandemic, considering fear, misinformation, structural challenges, among others, the reflection that a different look is needed for health with new investments so that the population do not suffer so much damage in case of a new pandemic situation, similar to the one experienced recently.